Fatigue in Survivors of Autoimmune Encephalitis. Issue 6 (13th November 2021) - Diaz-Arias, Luisa A.; Yeshokumar, Anusha Kierty; Glassberg, Brittany; Sumowski, James F.; Easton, Ava; Probasco, John C.; Venkatesan, Arun
Abstract : Background and Objectives: To evaluate the impact of fatigue after autoimmune encephalitis, determine associations with patients' characteristics, and identify factors that contribute to its development. Methods: In a first cohort recruited via several encephalitis support organizations, self-reported questionnaires were used to evaluate fatigue, depression, and sleep quality in adults after autoimmune encephalitis. In a second cohort where more in-depth clinical characterization could be performed, adults with encephalitis from 2 tertiary hospitals were evaluated using the same questionnaires. Patients' characteristics were retrospectively captured. Results: In the first cohort (mean [SD] age; 43 [16] years, 220 [65%] female), 220 of 338 participants (65%) reported fatigue, 175 of 307 (57%) depression, and 211 of 285 (74%) poor sleep quality. In the second cohort (48 [19] years; 43 [50%] women), 42 of 69 participants (61%) reported fatigue, whereas 23 of 68 (34%) reported depression and 44 of 66 (67%) poor sleep quality, despite more than 80% having "good" modified Rankin scale (mRS) scores (0–2). Individuals with anti-NMDA receptor encephalitis reported lower fatigue scores than those with other autoimmune encephalitis types. In a multivariate analysis examining factors at discharge that might predict fatigue scores, only anti-NMDA receptor encephalitis was a (negative) predictor of fatigue and remained so when potential confounders were included. Discussion: The impact of fatigue after autoimmune encephalitis is prominent and not fully accounted for by depression or sleep quality, nor adequately captured by mRS scores for disability. Fatigue is pervasive across autoimmune encephalitis, although lower scores are reported in anti-NMDA receptor encephalitis. Fatigue should be screened routinely, considered as an outcome measure in clinical trials, and further studied from a mechanistic standpoint.